2016
DOI: 10.1103/physrevb.94.024113
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength dependence of femtosecond laser-induced breakdown in water and implications for laser surgery

Abstract: The wavelength dependence of the threshold for femtosecond optical breakdown in water provides information on the interplay of multiphoton, tunneling and avalanche ionization, and is of interest for parameter selection in laser surgery. We measured the bubble threshold from UV to near-IR wavelengths and found a continuous decrease of the irradiance threshold with increasing wavelength λ. Results are compared to the predictions of a numerical model that assumes a bandgap of 9.5 eV and considers the existence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(101 citation statements)
references
References 137 publications
(267 reference statements)
4
90
1
Order By: Relevance
“…The mid‐point of the fluence range predicted by the model (F=7.35 mJ · cm 2) corresponds to ρe, max =1.75×1020 cm 3. This is very close to a recently reported threshold for bubble formation in pure water of ρ th =1.8×1020 cm 3 .…”
Section: Plasma Model Validationsupporting
confidence: 84%
See 2 more Smart Citations
“…The mid‐point of the fluence range predicted by the model (F=7.35 mJ · cm 2) corresponds to ρe, max =1.75×1020 cm 3. This is very close to a recently reported threshold for bubble formation in pure water of ρ th =1.8×1020 cm 3 .…”
Section: Plasma Model Validationsupporting
confidence: 84%
“…Nanoparticle‐mediated LIOB depends on the ionization energy, the level of impurities in the medium, nanoparticle morphology and concentration, and the laser beam properties (pulse duration, intensity and wavelength) . While the electric field enhancement in the vicinity of a nanoparticle is dependant on both morphology of the particle and the wavelength of irradiation, the optical breakdown threshold, I th , in pure water (as a model for biological media ) is also wavelength dependent . Linz et al.…”
Section: Wavelength‐dependence Of the Optical Breakdownmentioning
confidence: 99%
See 1 more Smart Citation
“…Such neuronal spatiotemporal coding has broad biological significance in areas ranging from synaptic mechanisms (Markram et al, 1997;Zhang et al, 1998;Stuart and Häusser, 2001), to sensory processing (Traub et al, 1996;Joris et al, 1998), to behavior (Schultz et al, 1997(Schultz et al, , 2017. We demonstrated that the high peak power of laser pulses from a fiber amplifier with a low repetition rate enabled suprathreshold photoactivation in vivo using excitation intensity (on average Յ0.2 mW/m 2 or 23 mW/cell for the three opsins) considerably below typical nonlinear photodamage thresholds (Koester et al, 1999;Hopt and Neher, 2001;Olivié et al, 2008;Linz et al, 2016). By comparison, reaching comparable temporal resolution with a scanning approach would require excitation intensity 100 -150 times higher Yang et al, 2018).…”
Section: Discussionmentioning
confidence: 92%
“…Yet setting the real limitations for multitarget 2P illumination requires considering possible sources of photodamage. These include both linear effects, such as thermal damage related to the linear absorption of light, and nonlinear, multiphoton absorption processes, inducing photochemical, ablation damage or optical breakdown (Hopt and Neher, 2001;Koester et al, 1999;Vogel et al, 2005) arising at peak fluences of about 0.1 J/cm 2 for Chinese hamster ovarian cells (Kö nig et al, 1999), 0.5-2 J/cm 2 in water (Linz et al, 2016;Noack and Vogel, 1999;Vogel et al, 2005), and 1.5-2.2 J/cm 2 for porcine corneal stroma (Olivié et al, 2008).…”
Section: Introductionmentioning
confidence: 99%